Seminar Dan Lokakarya Merawat Daya Kreativitas Siswa Untuk Guru Di SDN 032 Tilil Bandung - Bavadal, Fatimah; Sulistyo Setiawan; Agung Pramudya Wijaya; Dedy Ismail (LPPM Stikosa - AWS, 2024)
Creativity is a person's ability to be able to create new things with ideas, alternatives, and other possibilities that are useful in solving a problem. Basically, creativity is an ability that has been possessed by each individual which in the process these abilities must be trained and developed to be maximized properly. Creativity is also one of the important factors that can influence human growth and development, especially in early childhood who entering a golden age, where they begin to be sensitive to the surrounding environment. In this case creativity can be trained in a child with the help of parents and teachers as an impetus factor to create a passion for creative thinking. With the holding of seminars and workshops at SDN 032 Tilil, a problem was found that occurred in early childhood education, especially in schools, where teachers as teachers emphasized more material in the learning process, so that students could not have space for exploration to develop their ideas or ideas. One of the ways that teachers can do in schools is by creating a pleasant learning atmosphere and providing opportunities for students to be able to solve a problem through their sensitivity to the environment to produce solutions in the form of creative ideas or ideas. With a p;easant learning atmosphere, students can have new knowledge and experiences and can use their imagination to stimulate creative thinking that affects cognitive abilities in students.